Bilateral femoral agenesis in 3-month-old baby: A case report - Emiliana Susanti Foris; Mario Realino Nara; Defranky Theodorus (DiscoverSys Inc., 2022)
Background: Bilateral congenital femoral agenesis is a rare congenital anomaly. To our knowledge, there have only been three examples of simple congenital abnormalities linked to the femoral facial syndrome. We present a straightforward case of bilateral femoral agenesis in a 3-month-old female infant who did not have femoral facial syndrome and whose mother did not have diabetes. Discussion: Bilateral femoral agenesis is a rare and unusual anomaly; only six cases have been reported. Other structural are often involved; these include the acetabulum, musculature, vessels, and ligaments of the knee, tibia, fibula, and foot. In our case, there are no other anomalies found. The majority of cases, however, are sporadic; therefore, the parents may be reassured that the risk of further offspring being affected is negligible. The classification by Aitken is widely used. This classification is based on the severity of the hip and femur radiographic findings Case Presentation: A 3-month-old female baby presents with a complaint of short stature. The baby was born full term spontaneous labor, 2570 grams vigorous and started to cry immediately after birth. The mother has no history of diabetes, cigarette smoking, and exposure to teratogens. The parents were not related by blood. X-ray examination showed bilateral agenesis of the femur, normal tibia and fibula, and proximal cruris in lateral acetabula. Conclusion: Bilateral congenital femoral agenesis is a rare congenital anomaly. Although frequently related to maternal diabetes mellitus, there is no recognized cause for most cases.